2019
DOI: 10.1186/s12872-019-1111-6
|View full text |Cite
|
Sign up to set email alerts
|

CD36 gene polymorphism rs1761667 (G > A) is associated with hypertension and coronary artery disease in an Iranian population

Abstract: Background CD36 is associated with regulation of lipid metabolism, atherosclerosis, and blood pressure. Moreover, its variation may be involved in the development of hypertension and/or coronary artery disease (CAD). The present study was conducted to investigate the possible association of CD36 rs1761667 (G > A) polymorphism with hypertension and/or CAD in the southeastern of Iran. Methods The present observational study was composed of 238 subjects who were admitted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
(37 reference statements)
0
21
1
Order By: Relevance
“…General characteristics of the 18 eligible studies are provided in Table 1 . Six studies were from Asia 7 , 15 , 19 , 25 – 27 , five from African 8 , 11 , 20 22 , and six from Europe 13 , 14 , 17 , 18 , 23 , 24 ,and one study was from the USA/Italy 16 . The majority of eligible studies included both sexes and only two 20 , 27 and one 17 studies were performed on women and men, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…General characteristics of the 18 eligible studies are provided in Table 1 . Six studies were from Asia 7 , 15 , 19 , 25 – 27 , five from African 8 , 11 , 20 22 , and six from Europe 13 , 14 , 17 , 18 , 23 , 24 ,and one study was from the USA/Italy 16 . The majority of eligible studies included both sexes and only two 20 , 27 and one 17 studies were performed on women and men, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The participants were aged 18–75.73 years and the mean body mass index was ranged from 21.66 to 34.60 kg/m 2 . Seven studies were conducted on healthy individuals 16 18 , 20 , 21 , 23 , 27 , three studies targeted patients with heart diseases 7 , 8 , 19 , one study included individuals with T2DM 25 , metabolic syndrome 11 , and the six remaining studies included adults with other health status 13 – 15 , 22 , 24 , 26 . In the majority of studies, genotype distributions were in HWE 7 , 11 , 13 , 15 , 16 , 21 , 22 , 24 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies have clearly suggested that the genetic variant was associated with clinical outcomes, including lower rates of hypertension, coronary artery disease and liver fibrosis (33)(34)(35) .…”
Section: Discussionmentioning
confidence: 99%
“…In studies of Tunisian (13) and Algerian individuals (32) , individuals with the AA mutant genotype showed lower intensity of fat perception and a preference for added fat and oil; hence, these individuals had higher fat intake than individuals with the genotype with the G allele (2) . Additionally, studies have clearly suggested that the genetic variant was associated with clinical outcomes, including lower rates of hypertension, coronary artery disease and liver fibrosis (33)(34)(35) . The association between the variation in CD36 and fat sensing may be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association study (GWAS) revealed many gene polymorphisms such as PNPLA3 rs738409 and TM6SF2 rs58542926 which were the significant risk factors for NAFLD [12, 13]. Abundant studies revealed that gene polymorphisms such as CD36 rs1761667, CDKN2BAS rs496892, and COX2 -765G > C were tightly associated with the risk of CHD in different countries [1416]. Tribbles 1 ( TRIB1 ) encoding Tribbles protein homolog 1 [17], proteins from the tribbles family include a MEK1-binding domain, an E3 ubiquitin ligase (COP1)-binding domain, and a pseudokinase domain, all of which are significant by interacting with respective partners [18].…”
Section: Introductionmentioning
confidence: 99%